2011
DOI: 10.1117/1.3543814
|View full text |Cite
|
Sign up to set email alerts
|

Synoptic view of Dyakonov–Tamm waves localized to the planar interface of two chiral sculptured thin films

Abstract: The Dyakonov-Tamm wave combines the features of the Dyakonov wave and the Tamm electronic state. Dyakonov-Tamm waves guided by the planar interface of two dissimilar chiral sculptured thin films (STFs) were systematically examined. The interfaces result from the chiral STFs being dissimilar in (a) orientation about the helical axis, (b) structural handedness, (c) structural period, (d) vapor incidence angle, (e) material, or (f) various combinations thereof. A boundary-value problem for the propagation of Dyak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This multiplicity of Rayleigh waves contrasts with the single Rayleigh wave that exists for the homogeneous elastic solid obtained by making the CTSCM’s period either infinitely large or very small. Parenthetically, the observed multiplicity of Rayleigh waves guided by the traction-free surface of a periodically non-homogeneous half-space mirrors findings for electromagnetic surface waves wherein periodic non-homogeneity delivers a multiplicity of Tamm waves [ 57 ] and Dyakonov–Tamm waves [ 58 ] at a fixed frequency.…”
Section: Closing Remarksmentioning
confidence: 54%
“…This multiplicity of Rayleigh waves contrasts with the single Rayleigh wave that exists for the homogeneous elastic solid obtained by making the CTSCM’s period either infinitely large or very small. Parenthetically, the observed multiplicity of Rayleigh waves guided by the traction-free surface of a periodically non-homogeneous half-space mirrors findings for electromagnetic surface waves wherein periodic non-homogeneity delivers a multiplicity of Tamm waves [ 57 ] and Dyakonov–Tamm waves [ 58 ] at a fixed frequency.…”
Section: Closing Remarksmentioning
confidence: 54%
“…Whereas a Tamm wave can propagate parallel to any direction in the interface plane (without any dependence on the direction of propagation), Dyakonov-wave propagation can occur only in very limited ranges of the direction of propagation [19]-a feature that inhibited the experimental verification of the existence of Dyakonov waves until 4 years ago [24]. The range of the direction of propagation of Dyakonov-Tamm waves in the interface plane is much wider [23,[25][26][27] than that of Dyakonov waves, and can even be the full 360°.…”
Section: Introductionmentioning
confidence: 97%
“…Typically, only one ESW can propagate in a given direction in the interface plane at a specified frequency, if both partnering mediums are homogeneous [1][2][3], but there are exceptions [16]. However, if one of both of the partnering mediums are periodically nonhomogeneous in the direction normal to the interface, it is possible to trigger at the same time the propagation of more than one ESW, each with its own propagation characteristics [17][18][19][20][21][22][23]. In some instances it has been observed that two ESWs propagate with complex-valued wavenumbers that are very close to each other giving rise to a sort of a doublet [24,25].…”
Section: Introductionmentioning
confidence: 99%